Modal Analysis Of CNC Milling Machine Bed Made Of Different Alloys Using Finite Element Modeling - Omar, Mohd Hazri; Abdul Halim, Mohamad Nazri; Othman, Mohd Fadzli (JMPM (Jurnal Material dan Proses Manufaktur), 2023)
Over the years, there has been a strong emphasis on predicting the dynamic behavior of machine tool structures by identifying modal parameters. The machine bed is one of the most significant components in a CNC milling machine because its functionality significantly affects the final product's quality. The bed acts as the machine's foundation, supporting all of the machine's critical components. It is also utilized to avoid deformation caused by static and dynamic loads. This study aims to compare the modal parameters of several alloys used as bed materials, such as carbon steel, alloy steel, and stainless steel, to those of a common material. A three-dimensional model and modal analysis of the bed were conducted in Autodesk Inventor software. Alloy steel shows the highest values of natural frequencies compared to other materials due to its high Young’s modulus and low density. Similar mode shape is observed with varied magnitude in all the materials. According to the findings, alloy steel could be a viable alternative to cast iron in machine tools bed's structure